Evaluation of the Budgetary Practice as a Financial Tool - Mirdan, Alnujaimi Aws Aseed (Advances in Social Sciences Research Journal, 2020)
In financial accounting, there are assorted tools and approaches to keep track of the business activities. These tools are required so that the overall planning and predictions can be done. Budgetary practice or simply the budget based planning makes use of the techniques so that the financial liabilities and the growth factors can be evaluated effectively. Budgeting is one of the key practices for the financial goals and the data based activities for final prediction and the outcome with greater degree of accuracy. This manuscript is having the focus on the presentation of key aspects of budgetary planning or practice as the key financial tool in the business organizations.